UJI AKTIVITAS FRAKSI EKSTRAK BIJI BELIGO (Benincasa hispida Thunb. Cogn) TERHADAP PENURUNAN KADAR GLUKOSA DARAH MENCIT - M. Rusdi (Universitas Islam Negeri Alauddin Makassar, 2020)
This research aims to determine the faction activity of n-hexane, ethyl acetat, and 70% beligo seeds (Benincasa hispida Thunb. Cogn) on the decrease in blood glucose levels in mice. The research method includes extraction of samples by macerasion using 96% liquid of ethanol filter. This research used 25 male mice as he test animals which were divided into 5 treatment groups. Mice were fasted for 8 hours before treatment, then measurement of initial glucose levels, after that they were induced with 10% glucose and glucose levels were measured after induction. Group I was given 0,5% Na-CMC suspense as negative control, group II was given the n-hexane fraksion, group III was given ethyl acetate fraction, group IV was given 70% ethanol fraction and group V was given 0,013 mg/20 g BB glibenclamide suspension as positive control. Giving is done perorally with a volume of 1 ml. The results showed that the faction of n-hexane, ethyl acetate, and 70% ethanol extracts of beligo seeds (Benincasa hispida Thunb. Cogn) with a dose 28 mg/20 g BB had activity in decreasing blood glucose levels in mice (Mus musculus).